(untitled) (Jurnal Destinasi Pariwisata, 2026)
The purpose of this study was to identify and analyze the promotional strategies implemented by the Sam Poo Kong Temple management and to explain how these strategies contribute to attracting tourists. This study used a purposive sampling technique, which involves deliberately selecting informants based on specific criteria relevant to the research objectives. The population included the Sam Poo Kong Temple management, promotion/marketing staff, and tourists who had previously visited the temple. This population consisted of 12 people: 2 managers and 10 visitors. The results showed that the promotion of the Sam Poo Kong Temple was carried out using a mix of digital and conventional strategies, involving routine annual promotional activities and the use of digital and direct media. The promotion of the Sam Poo Kong Temple was quite effective in increasing tourist interest. This is evident from the most influential sources of information being interactive social media and personal experiences, particularly promotional videos on TikTok.